Experimental exposure assessment for in vitro cell-based bioassays in 96- and 384-well plates - Huchthausen, Julia; König, Maria; Escher, Beate I.; Henneberger, Luise (Frontiers in Toxicology, 2023)
In vitro cell-based bioassays have great potential for application in human health risk assessment of chemicals. Quantification of freely dissolved concentrations (Cfree) in in vitro assays is essential to generate reliable data for in vitro-to-in vivo extrapolation. Existing methods for the quantification of Cfree are limited to low-throughput microtiter plates. The present study is a proof-of-principle for the applicability of a solid-phase microextration (SPME) method for the determination of Cfree in the peroxisome proliferator-activated receptor gamma (PPARγ) bioassay run in 384-well plates with 80 µL medium per well. The effect concentrations obtained from 384-well plates were compared with those from 96-well plates from a previous study. Nominal effect concentrations agreed within a factor of three between 96-well and 384-well plates and freely dissolved effect concentrations agreed within a factor of 6.5 between both plate formats. The good agreement of the results from both plate formats prove the general applicability of the SPME method for the determination of Cfree for bioassays in 384-well plates, making the present study a first step towards exposure assessment in high-throughput bioassays.